A Comparative Review of Nonparametric Statistics Textbooks. Issue 4 (2nd October 2019) - Richardson, Alice
ABSTRACT: In this article I will review six textbooks commonly set in University undergraduate nonparametric statistics courses. The books will be evaluated in terms of how key statistical concepts are presented; use of software; exercises; and location on a theory-applications axis and an algorithms-principles axis. The placement of books on these axes provides a novel guide for instructors looking for the book that best fits their approach to teaching nonparametric statistics.